The Role of Non-State Actors in Establishing the Halal Ecosystem in Indonesia - Nursita, Rizki Dian; Adelia, Devi; Septiani, Retno; Widyaputri, Primadiani Difida (Department of International Relations, Hasanuddin University, 2024)
Amidst the global growth of the Muslim population, the need for products or services that comply with sharia law has become unavoidable. As the country with the largest Muslim population in the world, Indonesia has declared itself to become a major player in the global halal industry. This can be seen from the changes made by Indonesia in the last decade, both in policy and governance aspects to form an effective halal sector ecosystem as planned in the Indonesia Islamic Economic Masterplan 2019-2024. However, amid several policies implemented by the government, the role of non-state actors, including but not limited to large industries, business groups and MSMEs, community organizations or NGOs, and product influencers, increases and mainstreaming the halal industry in Indonesia cannot be ruled out. Based on a study of several literature related to the halal industry in Indonesia, researchers see that most of the research on the halal industry in Indonesia focuses on discussing strategy and the government as well as opportunities and challenges for Indonesia in developing the halal industry. Therefore, the study aims to discuss the role of non-state actors in forming the halal industrial ecosystem in Indonesia.